2007
DOI: 10.1089/aid.2006.0299
|View full text |Cite
|
Sign up to set email alerts
|

A Nascent HIV Type 1 Epidemic among Injecting Drug Users in Kabul, Afghanistan Is Dominated by Complex AD Recombinant Strain, CRF35_AD

Abstract: Injecting drug use (IDU), common in global centers of heroin production, confers significant risk for HIV-1 infection. Once introduced into IDU networks, an explosive rise in HIV-1 infection typically occurs, fueled principally by needle sharing. New HIV-1 epidemics in IDUs have occurred in Russia, China, Thailand, Spain, Iran, and in other countries, and some have spread into other risk groups in their respective countries. In Afghanistan, the introduction of HIV-1 into IDU networks has begun, but a recent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Subtype AD, which is also a variant of A, has been reported from IDUs in Afghanistan and Iran in 2007, 15 while two separate studies in Manipur have reported subtype C as the predominant subtype among IDUs in India. 16,17 ARV drug resistance rates were 7.4% in East Asia and 5.7% in Southeast Asia, 3 but we found a higher rate (21.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Subtype AD, which is also a variant of A, has been reported from IDUs in Afghanistan and Iran in 2007, 15 while two separate studies in Manipur have reported subtype C as the predominant subtype among IDUs in India. 16,17 ARV drug resistance rates were 7.4% in East Asia and 5.7% in Southeast Asia, 3 but we found a higher rate (21.2%).…”
Section: Discussionmentioning
confidence: 99%
“…10 Descriptive statistics were generated for genotyped samples. Phylogenetic analysis was with PHYLIP, including SEQ-BOOT, DNADIST, NEIGHBOR, and CONSENSE modules, and trees were constructed with Treetool.…”
Section: Sanders-buell Et Almentioning
confidence: 99%
“…The analyzed subregions (gag p 17 and ENV C1-C5) revealed close homology between the Hirat IDU specimens and with the previously described Kabul specimens (data not shown). 10 The relations among the Hirat strains were also informative. Among these 10, three distinct subclusters comprised two or three strains, whereas two other Hirat strains were generally equidistant from the Kabul strains.…”
Section: Sanders-buell Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…3 (NAM-RU-3) was requested by MoPH to assist with rebuilding the country's laboratory capacity and improving current syndromic disease surveillance systems based on its earlier collaborations in tick collection, vector identification and human immunodeficiency virus research [7][8][9][10]. In this paper, we describe the methods used by NAMRU-3 in strengthening laboratory capacity building in Kabul and outlying regions.…”
Section: Introductionmentioning
confidence: 99%